Prospects for Achieving the Sustainable Development Goals in Ukraine to Reduce Mortality Due to Non-Communicable Diseases: The Impact of the Covid-19 Pandemic and russian Aggression - Ryngach N. О. (Statistics of Ukraine, 2023)
Today, in Ukraine, as in the world, non-communicable diseases (NCDs) are an urgent problem that goes beyond public health. NCDs determine significant economic and demographic losses as a result of temporary and permanent incapacity for work, a drop in labor productivity, costs of medical care and premature mortality. More than 86% of premature deaths from NCDs occur in low- and middle-income countries, including Ukraine. Reducing premature mortality from non-communicable diseases was chosen as one of the targets of the 2030 Agenda for Sustainable Development under Goal 3 Good health and well-being. A threat to the achievement of this and related targets of the Sustainable Development Goals (SDG) in the world and in Ukraine was the successive combined negative impact of a complex of factors due to the pandemic of the coronavirus disease and the aggression of the Russian Federation. The aim of the work is to assess the dynamics of mortality due to non-communicable diseases by selected causes of death based on the monitoring of national indicators of the achievement of the Sustainable Development Goals in Ukraine within the framework of the targets of Goal 3. Good health and well-being; identify and analyze a complex of factors related to the COVID-19 pandemic and Russia’s aggression that influence these changes; substantiate the assumptions regarding the prospects for the implementation of the targets set by the country in the 2030 Agenda for Sustainable Development in the area of the epidemiological situation regarding non-communicable diseases (in particular, regarding the reduction of mortality from them). The assessment of the pre-war situation and changes during the COVID-19 pandemic for the period 2019–2021 was carried out on the basis of data from the State Statistics Service of Ukraine on mortality from non-communicable diseases, which correspond to selected national indicators and data from the monitoring of indicators of SDG: Ukraine. The Sustainable Development Goals Report 2021, 2022, 2023 and data from the National Cancer Registry of Ukraine were used. Due to complications in obtaining, summarizing and analyzing statistical data on mortality in Ukraine with the beginning of the large-scale invasion of the Russian Federation, assumptions about mortality shifts according to selected national indicators of the implementation of the targets of the 2030 Agenda for Sustainable Development are limited by directions. As of 2021, the COVID-19 pandemic has slowed progress towards achieving the Sustainable Development Agenda in terms of reducing premature mortality from NCDs: according to four of the six national indicators that track progress in this area (3.4.1, 3.4.4, 3.5.1, and 3.5.2) there was a deviation from the planned trajectory and an excess of intermediate results for 2020. The aggression of the Russian Federation in Ukraine threatened to an even greater extent the implementation of measures aimed at achieving the selected indicators. Mortality from NCDs (primarily from cardiovascular diseases) is projected to increase by 2022, as well as in the period before the end of the war and in the immediate period after, with a widening gap between the mortality rates of men and women. In particular, with a high degree of probability, we can expect in the coming years, an increase in morbidity and mortality due cerebrovascular diseases, as well as a "rejuvenation" of the age at which a cerebrovascular disaster occurs. The main factors, the synergistic effect of which has already determined and will determine in the near future an increase in the risk of dying due to non-communicable diseases, including prematurely, are the difficulty of access to the necessary medical services and medicines; decrease in their availability, including economic, with growing dissatisfaction with the needs of people with NCDs in medical care; disruption of the functioning of medical institutions; delay / inability to receive necessary treatment; increasing the influence of the main risk factors and reducing the possibilities of their minimization; the presence of the majority of the population in a state of stress and the prevalence of the practice of overcoming it due to excessive use of alcohol and tobacco; immediate and distant consequences of the transferred coronavirus disease, especially Long COVID; reduced adherence to treatment and lifestyle changes, etc. With every day of the war, the threat of non-fulfillment (incomplete fulfillment) of the tasks set within the framework of Goal 3 to reduce mortality due to NCDs in Ukraine by 2030 deepens. There is a need to review and update national tasks taking into account existing threats and challenges, including in the field of NCDs.